Myrcia auxotelica, a new southeastern Brazilian Myrtaceae - Sobral, Marcos; Antunes, Kelly (Phytotaxa, 2018)
The American genus Myrcia De Candolle (1827: 406) comprises about 850 species (Lucas et al. 2018), from which about 260 occur in Brazil (BFG 2015). Along the examination of some unidentified specimens we spotted a singular Myrcia from southeastern Brazil that we here propose as new. Herbaria are cited according to Thiers (2018); measurements are in the order length × width, and when only one measurement is presented it refers to length except otherwise stated.